Capacity of Decomposed Methylene Blue and Anticancer Effects of Silver Nanoparticles Using Perilla Leaf Extract - Hoang Phu, Hiep; Doan Duc, Hieu; Chu Anh, Nguyet; Do, Hue (Science & Technology Asia, 2024)
Silver nanoparticles (AgNPs) are one of the materials with a lot of potential because of their diverse applications. AgNPs are synthesized in a variety of ways; however, with the direction of anticancer applications and decomposition of organic dyes in dyeing wastewater, AgNPs synthesized by the green method are preferred. In this study, AgNPs were synthesized using Perilla frutescens (L.) Britt extract called P. AgNPs. The Perilla frutescens (L.) Britt extract was utilized as both a surface stabilizer and a reducing agent. UV-Vis absorption spectra of the P.AgNPs was analyzed to determine how particle production is affected by the extract's pH. The shape, crystalline structure, size and size distribution of P.AgNPs were studied using TEM imaging, X-ray diffraction diagram (XRD) and dynamic light scattering (DLS). Surface functional groups and atomic composition of P. AgNPs are represented on Fourier Transformation InfraRed spectrum (FTIR) and Energy-dispersive X-ray spectroscopy (EDX). The obtained P.AgNPs are relatively uniform with an average diameter of 30 nm ± 5 nm and well distributed in the solution. P.AgNPs were deposited on activated carbon (P.AgNP-AC). P. AgNPs- AC was used to decompose methylene blue (MB) dye in the presence of H2O2, achieving a decomposition efficiency of up to 98. 4%. The extract or P. AgNPs exhibited potential antiproliferative activity against MDA-MB-231, HT29, and K562 cells. Interestingly, the anticancer effect of P. AgNPs was up to 2.0 times stronger than that of the leaf extract.